2020
DOI: 10.35495/ajab.2019.04.174
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating water stress on wheat through foliar application of silicon

Abstract: Climate change emerges in different forms such as drought, which is prevalent all over the world, especially in semi-arid and arid regions. Crop production especially wheat (Triticum aestivum L.) yield is affected due to water shortage at critical growth stages in Pakistan. A greenhouse experiment was conducted by using plastic trays to assess the performance of wheat to exogenous silicon (Si) application under water stress which in applied through skipping irrigation at critical stages at College of Agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In the agricultural sector, proficient water administration drives the handling of all possible routes for water demand and supply management approaches [17][18][19]. In Pakistan, Qamar et al [20] reported that the productivity of field crops was highly dependent upon the availability of inputs, particularly water, at the critical growth stage, as the crop yield was significantly reduced by water shortage. Application of conservation tillage, stress signaling elements, plant water extracts, osmo-protectants and synthetic and natural mulches and the growth of drought-tolerant varieties are various practices and approaches that can be used to mitigate the adverse impacts of drought stress [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In the agricultural sector, proficient water administration drives the handling of all possible routes for water demand and supply management approaches [17][18][19]. In Pakistan, Qamar et al [20] reported that the productivity of field crops was highly dependent upon the availability of inputs, particularly water, at the critical growth stage, as the crop yield was significantly reduced by water shortage. Application of conservation tillage, stress signaling elements, plant water extracts, osmo-protectants and synthetic and natural mulches and the growth of drought-tolerant varieties are various practices and approaches that can be used to mitigate the adverse impacts of drought stress [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Research, Society andDevelopment, v. 10, n. 4, e41610414232, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i4.14232 We highlight that in other crops of the Poeceae family, such as rice (Couto et al, 2020), sugarcane , maize (Oliveira et al, 2020a), sorghum (Flores et al, 2018a;Oliveira et al, 2019;Oliveira et al, 2020a), and wheat (Qamar et al, 2020), foliar supply of soluble Si sources has been shown to be efficient to increase the uptake and accumulation of the beneficial element. Si usually has low mobility in the phloem, being considered little mobile in plants (John & Raven, 1983;Raven, 2001;Malavolta, 2006), suggesting the need for studies on highly soluble Si sources for supply to crops.…”
Section: Discussionmentioning
confidence: 93%
“…Another important feature is its ability to accumulate silicon (Si) (Epstein, 2009). Although studies on Si for this crop are incipient, its application has shown promising results, increasing yield when applied to Si-accumulating plants such as rice (Couto et al, 2020), sugarcane , maize (Oliveira et al, 2020a), sorghum (Flores et al, 2018a;Oliveira et al, 2020a), sunflower (Flores et al, 2018b;Peixoto et al, 2020), industrial processing tomato (Moraes et al, 2020), and wheat (Qamar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Qamar et al. (2020) stated that application of inorganic substances mitigates the adverse effects of abiotic stresses. AsA is widely distributed antioxidant in plants that has major role in scavenging reactive oxygen species produced during oxidative and various environmental stresses by donating electrons in different reactions (Sharma et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are also many synthetic plant growth promoters such as ascorbic acid (AsA) and hydrogen peroxide which play inevitable role to mitigate abiotic stresses in cereals. Qamar et al (2020) stated that application of inorganic substances mitigates the adverse effects of abiotic stresses. AsA is widely distributed antioxidant in plants that has major role in scavenging reactive oxygen species produced during oxidative and various environmental stresses by donating electrons in different reactions (Sharma et al, 2012).…”
mentioning
confidence: 99%